Anisotropic thermal transport in Weyl semimetal TaAs: a first principles calculation. Issue 25 (8th June 2016) - Ouyang, Tao; Xiao, Huaping; Tang, Chao; Hu, Ming; Zhong, Jianxin
Abstract : Distinct anisotropic thermal conductivity is observed in the Weyl semimetal TaAs. Abstract : A fundamental understanding of the phonon transport property is crucial to predict the thermal management performance in micro/nano-electronic devices. By combining first principle calculations and Boltzmann phonon transport equation, we investigate thermal transport in TaAs—a typical Weyl semimetal. The lattice thermal conductivity of TaAs at room temperature was found to be 39.26 W mK −1 and 24.78 W mK −1 along the a ( b ) and c crystal axis, respectively, showing obvious anisotropy. Detailed analyses of the mode level phonon properties further revealed that the three acoustic phonon modes dominate the overall thermal transport and the major phonon scattering channels in this typical Weyl semimetal were TA1/TA2/LA + O ↔ O and A + A ↔ O. The representative phonon mean free path of TaAs was also calculated in this paper, which provide helpful guidance for the thermal management of TaAs-based electronic devices.